MODELING SHIFTING GEOGRAPHICAL DISTRIBUTIONS OF LEAST CONCERN ASIAN BRACKISH FROG FEJERVARYA CANCRIVORA (GRAVENHORST, 1829) (ANURA: DICROGLOSSIDAE) IN WEST JAVA, INDONESIA RELATED TO CMIP 5 RCP 8.5 CLIMATE CHANGE SCENARIO - Andri Wibowo; Adi Basukriadi; Erwin Nurdin; Nana Suryana Nasution; Vita Meylani (Treubia, 2023)
Amphibians and their geographical distribution are threatened by climate change, including speciesin West Java, Indonesia. It is estimated that 300 amphibian species are threatened, including the familyDicroglossidae. At the same time, information on how climate change impacts amphibian species inIndonesia is very limited. This study aims to assess and model the suitable habitat for the least concernAsian brackish frog, Fejervarya cancrivora (Gravenhorst, 1829), under the CMIP 5 RCP 8.5 futureclimate change scenario by 2070, analyzed using Maximum Entropy (MaxEnt). The models developedwith MaxEnt showed good predictivity, with an AUC value of 0.701. The models that inform theprecipitation of the wettest month, isothermality, and mean diurnal range variables have significantcontributions to make in shaping F. cancrivora geographical distributions. The models confirm that F.cancrivora had shifted its geographical distribution and had gained and lost habitats under a future climatechange scenario by 2070. F. cancrivora will lose 4,428 km2 of its current habitat and will gain 2,673km2 of new habitat. In total, climate change will cause F. cancrivora to lose its habitat by 1,755 km2.